Waterbath Calibrator with Nine Channels Sensor - Mohammad Rofi'i; Syafudin Syaifudin; Dyah Titisari; Bedjo Utomo (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2019)
Water bath is a laboratory equipment that contains water or special liquid that can maintain the temperature under certain conditions during the specified time interval. For this reason, calibration is needed so that the temperature in the chamber waterbath is stable or not. calibration is carried out by comparing measuring instruments and measuring materials to be calibrated to traceable standards that are traceable to national and / or international standards. Based on the results of the identification of the problems mentioned above, the author makes a waterbath calibrator entitled